A comprehensive analysis of NAC gene family in Oryza sativa japonica: a structural and functional genomics approach. Issue 3 (11th February 2023) - Ray, Sujay; Basnet, Abishek; Bhattacharya, Shreya; Banerjee, Arundhati; Biswas, Koustav
Abstract: NAC gene family regulates diverse aspects of plant growth and developmental processes. The NAC DNA binding domains together with cis-acting elements play inter-related roles in regulating gene expression. In this study, an in silico approach for genome wide analysis of NAC gene in Oryza sativa japonica lead to an identification of 11 NAC genes, distributed over 12 chromosomes. A detailed analysis of phylogenetic relationship, motifs, gene structure, duplication patterns, positive-selection pressure and cis-elements of 11 OsNAC genes were performed. Three pairs of NAC genes with a high degree of homology in terminal nodes were observed and were inferred to be paralogous pairs. One conserved NAC domain was analyzed in all the NAC proteins. Only one gene was studied to be intronless and the majority had 2 introns. Segmental gene duplication pattern was predominant in 11 NAC genes. Ka/Ks ratio of 3 pairs of segmentally duplicated gene was substantially lower than 1, suggesting that the OsNAC sequences are under strong purifying selection pressure. NAC74 and NAC71 gene showed the maximum responsiveness for several factors. The paralogous genes, NAC2 and NAC67 were found to have maximum mya values, respectively. They showed maximum difference amongst themselves in all the categories of responsiveness. Responsiveness towards abscisic acid was observed to be absent in NAC67, but present in NAC2, while responsiveness to meristem inducibility was observed to remain absent in NAC2 but present in NAC67 . These results would provide a platform for the future identification and analysis of NAC genes in Oryza sativa japonica . Communicated by Ramaswamy H. Sarma